Pemikiran R.A. Kartini tentang Pendidikan Perempuan dan Relevansinya dengan Pendidikan Islam - ’Ainy, Mustachsana Qurrotu; Baidi, Baidi (Lembaga Yasin AlSys, 2025)
Women have long been a central issue in social studies, particularly in relation to educational access and gender equality. Prior to the 20th century, Indonesian women experienced marginalization, lacking freedom of thought and facing restricted roles in society. In response to this inequality, several female figures most notably R.A. Kartini emerged as pioneers of emancipation, advocating for women’s rights to receive proper education. This study aims to examine R.A. Kartini’s thoughts on women’s education and their relevance to the principles of Islamic education. Utilizing a qualitative method with a literature review approach, the research analyzes Kartini’s letters alongside supporting literature. The findings reveal that Kartini not only critiqued the patriarchal culture that constrained Javanese women, but also promoted educational values aligned with Islamic teachings, such as the importance of knowledge, justice, and the empowerment of women as a moral and humanitarian responsibility. Though rooted in a local context, Kartini’s ideas hold universal value and remain pertinent to contemporary challenges in Islamic education. The study concludes that Kartini’s struggle can serve as an inspiration for developing an Islamic education model that is responsive to gender equality issues, while remaining grounded in moral and spiritual values consistent with Islamic teachings.